Development and Validation of a UHPLC-DAD Method for the Quantitative Analysis of Major Dihydrochalcone Glucosides from Thonningia sanguinea VAHL - Pompermaier, Luca; Schwaiger, Stefan; Mawunu, Monizi; Lautenschlaeger, Thea; Stuppner, Hermann (Planta Medica, 2019)
Thonnigia sanguinea is a plant widely used in traditional African medicine against a variety of diseases. The obligate parasite is growing throughout tropical African forests and utilizes a large variety of hosts. Dihydrochalcone glucoside derivatives isolated from the subaerial parts of this plant were identified as potential antidiabetic lead compounds. In this study, an ultrahigh-performance liquid chromatographic method coupled with a photodiode array detector was developed for the quantitation of six major dihydrochalcone derivatives. The analytes were baseline separated in complex samples within 14 minutes on a Phenomenex Luna Omega 1.6 µm C18 column using a mobile phase consisting of water and acetonitrile (each + 0.01% trifluoroacetic acid) in gradient elution. Method validation confirmed the selectivity, linearity (R2 ≥ 0.9992), precision (inter-day ≤ 1.98%, intraday ≤ 2.00%), and accuracy (recovery rates of 97.4 – 106.3% for all analytes). At 280 nm, the LODs and LOQs were found to be lower than 1.42 and 4.30 µg/mL, respectively. Eight plant batches from the northern Angolan province of Uíge (collected in the wild or bought on markets) were extracted with methanol using an ultrasound-assisted extraction protocol and subsequently analyzed with the validated method. Results indicated high contents of dihydrochalcone glucosides in all eight samples. Most notably, the two bioactive constituents thonningianin A and B were present in fairly large amounts (2.42 – 5.35 w%).
Keywords: Thonningia sanguinea; Balanophoraceae; UHPLC-DAD; dihydrochalcone glucosides; thonningianin A; thonningianin B